2005
DOI: 10.1074/jbc.m411886200
|View full text |Cite
|
Sign up to set email alerts
|

Xenopus laevis CYP17 Regulates Androgen Biosynthesis Independent of the Cofactor Cytochrome b5

Abstract: The enzyme CYP17 primarily regulates androgen production by mediating four reactions: conversion of pregnenolone and progesterone to 17-hydroxypregnenolone and 17-hydroxyprogesterone, respectively (17␣-hydroxylase activity), followed by conversion of the 17-hydroxylated steroids to dehydroepiandrosterone and androstenedione, respectively (17,20-lyase activity). Most mammalian CYP17 isoforms have high 17␣-hydroxylase relative to 17,20-lyase activities and preferentially mediate one of the two 17,20-lyase reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Interestingly, a CYP17 from Xenopus laevis displayed unusually high lyase activity in the absence of either frogor human-derived cytochrome b 5 (Yang & Hammes 2005). Moreover, the rate of cleavage activity of Xenopus laevis CYP17 in the absence of cytochrome b 5 was found to be similar to human CYP17 assayed in the presence of human cytochrome b 5 .…”
Section: Additional Factors That Modulate Cyp17 Cleavage Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, a CYP17 from Xenopus laevis displayed unusually high lyase activity in the absence of either frogor human-derived cytochrome b 5 (Yang & Hammes 2005). Moreover, the rate of cleavage activity of Xenopus laevis CYP17 in the absence of cytochrome b 5 was found to be similar to human CYP17 assayed in the presence of human cytochrome b 5 .…”
Section: Additional Factors That Modulate Cyp17 Cleavage Activitymentioning
confidence: 82%
“…The identity of such residues on the surface of cytochrome b 5 may similarly be vital for CYP17 cleavage. More recently, residues 16-41 in human cytochrome b 5 were found to be necessary in the specific regulation of the lyase activity of human CYP17, possibly serving as an interacting domain with the enzyme (Yang & Hammes 2005). Indeed, further detailed identification of the key residues for CYP17 and cytochrome b 5 interaction will give insight into the nature of interaction between cytochrome b 5 and CYP17 and shed light on how cytochrome b 5 is able to promote a subtle conformational change of CYP17.…”
Section: Future Prospectsmentioning
confidence: 99%
“…It is interesting to note that Xenopus P450c17 exhibits similar rates of hydroxylation of P4 and cleavage of 17αOH P4 as the mammalian enzymes presented here while metabolism of P5 is much lower than P4 by comparison and more typical of the guinea pig enzyme. However, unlike C17,20-lyase activities of the porcine, guinea pig, and bovine enzymes that were similarly stimulated, 3 to 5-fold, in the presence of b 5 , the Xenopus C17,20-lyase activity exceeded the rate of 17α-hydroxylation and was not stimulated by b 5 (Yang and Hammes, 2005). Therefore, it will be of interest to extend the current study to other P450c17s to determine if specific patterns of amino acid sequences can be distinguished relating differences in enzymatic properties with differences in their amino acid sequences.…”
Section: A-hydroxylase/c1720-lyase Activitiesmentioning
confidence: 49%
“…The OH-P and AD concentrations in the assay medium were measured initially and following the reaction with ELISA as described above. CYP17 17,20-lyase activity was confirmed in accordance with the methods of Auchus, Lee and Miller (1998) and Yang and Hammes (2005) with modifications. For the measurement of CYP17 17hydroxylase and 17,20-lyase activity, approximately 0.5 g of gonad tissue was homogenized in cold 0.05 M Tris buffer (pH 7.4).…”
Section: Cyp17 Analysis and Testosterone Synthesismentioning
confidence: 79%
“…(2) a 17,20-lyase activity, which metabolizes the 17-hydroxylated progestins to dehydroepiandrosterone and androstenedione (AD), respectively. Yang and Hammes (2005) have shown that sexually mature X.…”
Section: Introductionmentioning
confidence: 99%